Anemia, intractable vomiting, chronic diarrhea, and syndrome of inappropriate antidiuretic secretion: a diagnostic dilemma. Issue 52 (December 2017) - Tariq, Hassan; Kamal, Muhammad Umar; Reddy, Pavithra; Bajantri, Bharat; Niazi, Masooma; Matela, Ajsza; Zeana, Cosmina; Ihimoyan, Ariyo; Dev, Anil; Chilimuri, Sridhar
Abstract: Rationale: Strongyloidiasis hyperinfection and disseminated disease have high mortality rates due to several complications and early detection of Strongyloides infection is therefore prudent. Patient concerns: A 37-year-old male patient came with chronic diarrhea, intractable vomiting and was found to have hyponatremia, and anemia on the initial laboratory tests. Diagnoses: Further work up revealed syndrome of inappropriate antidiuretic secretion to be the cause of the hyponatremia in addition to gastrointestinal loses. His hospital course was complicated by persistent hyponatremia and later development of partial small bowel obstruction. Interventions: Considering his symptoms we had a suspicion of small bowel pathology for which he underwent an esophagogastroduodenoscopywith biopsies that revealed strongyloidosis as the cause of his symptoms. He was also found to have human T-cell lymphotropic virus infection, likely contributing to the disseminated disease. Outcomes: He was started on ivermectin with complete resolution of symptoms and improvement of hyponatremia. Lessons: It is very important to suspect Strongyloides infection in a patient presenting with syndrome ofinappropriate antidiuretic secretion as hyperinfection and disseminated disease can be life threatening without antihelmintic therapy.